The Uneven Later Work Course: Intersectional Gender, Age, Race, and Class Disparities. (4th March 2021) - Moen, Phyllis; Flood, Sarah M; Wang, Janet
Abstract: Objectives: Later adult work attachments and exits are in flux, suggesting the need for understanding both the range of contemporary population-level pathways of work and nonwork and variations by overlapping social locations. We document patterned continuity and change in monthly work attachments and analyze the intersecting effects of age, gender, education, and race/ethnicity. Methods: We capitalize on massive microlevel 16-month panel data from the Current Population Survey from 2008 through 2016 to empirically identify patterned pathways of monthly states: working full-time, long hours, part-time; being self-employed or unemployed; not working because of a disability, due to family care or other reasons, or because one defines oneself as retired. Results: Analyses of 346, 488 American women and men aged 50–75 years reveal patterned elasticity in the timing and nature of work attachments in the form of six distinctive pathways. Our intersectional analyses illustrate divergences and disparities: advantages for educated White men, disadvantages for low-educated Black men and women through their early 60s, and intersecting effects of gender, education, and race/ethnicity during the later work course across age groups. We find convergence across social markers by the 70s. Discussion: This research highlights the importance of intersectional analysis, recasting the gendered work course in later adulthood into a framework of even greater complexities within mutually shaping categories of race/ethnicity, class, and age. Older Americans experience patterned, uneven pathways around work and nonwork. We recommend additional scholarship on the dynamics of constrained and disparate choices unfolding across multiple intersecting social locations.